Risk Taking in Winner-Take-All Competition - Matthias Kräkel; Petra Nieken; Judith Przemeck (University of Bonn, Bonn Graduate School of Economics (BGSE), 2008)
We analyze a two-stage game between two heterogeneous players. At stage one, common risk is chosen by one of the players. At stage two, both players observe the given level of risk and simultaneously invest in a winner-take-all competition The game is solved theoretically and then tested by using laboratory experiments. We find three effects that determine risk taking at stage one - an effort effect, a likelihood effect and a reversed likelihood effect. For the likelihood effect, risk taking and investments are clearly in line with theory. Pairwise comparison shows that the effort effect seems to be more relevant than the reversed likelihood effect when takin risk.
Keywords: M51; C91; D23; 330; Tournaments; Competition; Risk-Taking; Risikopräferenz; Extensives Spiel; Wettbewerb; Spieltheorie